2018
DOI: 10.4236/ojmn.2018.81009
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgically Treated Acute Traumatic Epidural Hematomas Based on the Glasgow Coma Scale

Abstract: This study was a retrospective analysis of outcome of surgically treated acute traumatic epidural hematomas based on the Glasgow coma scale. The series enrolled forty-six consecutive cases of acute traumatic epidural hematomas. The mean age of patients was 29.56 years and 63.04% of the patients were between 21 and 30 years of age. Forty-tree out of 46 (93.47%) of the patients were males. Road traffic crash was the main mode of injury. The severity of the traumatic brain injury was classified according to the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The findings of the study showed that GSC score of the patients at the time of admission is significantly associated with the outcome (p<0.001). The similar findings were noted in the study conducted by Ndoumbe A et al in which GCS score at the time of admission was strongly predictive for good or poor outcome (19). In this study GCS score of the patients at the time of surgery was also found to be significantly associated with outcome of EDH (p<0.001)Which is consistent with the findings of Khan MB et al in which they observed that time since trauma and surgery were directly related to outcomes and that surgical delay beyond 12 hours resulted in statistically significant worse outcomes (20).…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the study showed that GSC score of the patients at the time of admission is significantly associated with the outcome (p<0.001). The similar findings were noted in the study conducted by Ndoumbe A et al in which GCS score at the time of admission was strongly predictive for good or poor outcome (19). In this study GCS score of the patients at the time of surgery was also found to be significantly associated with outcome of EDH (p<0.001)Which is consistent with the findings of Khan MB et al in which they observed that time since trauma and surgery were directly related to outcomes and that surgical delay beyond 12 hours resulted in statistically significant worse outcomes (20).…”
Section: Discussionsupporting
confidence: 89%
“…Other studies states that there is a correlation between patients GCS score with CT scan results in EDH patients [19]. Another research shows that there is a negative correlation between bleeding volume and GCS score in intracerebral haemorrhage patients who have a correlation value of 0.599 or shows a moderate correlation, whereas other research at North Phanom Hospital states that there is a significant correlation between GCS scores and bleeding volume in the incident of head injury with a p value <0.001.…”
Section: Discussionmentioning
confidence: 96%
“…Ndoumbe et al retrospectively analyzed 46 patients with traumatic AEDH based on GCS score. The results demonstrated that the GCS score was a good predictor of prognosis, and all survivors with unfavorable outcome had GCS ≤ 8 on admission ( 12 ). Our results showed that 52.94% of patients with swirl sign had a GSC score of 3–8 on admission, a percentage significantly higher than that of patients without swirl sign (21.93%).…”
Section: Discussionmentioning
confidence: 99%